2015
DOI: 10.15356/0373-2444-2014-3-5-18
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of changes of land cover using multispectral remote sensing information in the central forest reserve

Abstract: Институт проблем экологии и эволюции им. А.Н. Северцова, РАН Центрально-лесной государственный заповедник. Нелидовский р-н, Тверская обл. Поступила в редакцию 28.05.2012 г. По результатам анализа различий отражения солнечной радиации в спектральных каналах в двух сценах спутника Landsat за март 1986 г. и март 2010 г. установлен масштаб и характер изменений растительного покрова, для которого выявлен баланс между разрушением и восстановлением. Небольшое нарушение баланса происходит в результате жизнедеятельност… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 2 publications
(2 reference statements)
0
5
0
Order By: Relevance
“…It can be assumed that, in terms of its parameters, the climate of the territory shifts towards the Atlantic period (6–7 thousand years ago), which, according to dating, marks the beginning of the formation of raised bogs on the territory of the Reserve [ 86 ]. Our analysis of the dynamics of the Reserve’s vegetation cover in recent years [ 87 ] and field observations show an increase in the renewal of broad-leaved tree species (maple, linden, hazel) in well-drained and warm relief positions and the expansion of sphagnum mosses in well-lit glades and under the forest canopy on flat and concave landforms. We also recorded an unambiguous increase in the areas of raised bogs, accompanied by waterlogging and drying out of adjacent forests.…”
Section: Discussionmentioning
confidence: 99%
“…It can be assumed that, in terms of its parameters, the climate of the territory shifts towards the Atlantic period (6–7 thousand years ago), which, according to dating, marks the beginning of the formation of raised bogs on the territory of the Reserve [ 86 ]. Our analysis of the dynamics of the Reserve’s vegetation cover in recent years [ 87 ] and field observations show an increase in the renewal of broad-leaved tree species (maple, linden, hazel) in well-drained and warm relief positions and the expansion of sphagnum mosses in well-lit glades and under the forest canopy on flat and concave landforms. We also recorded an unambiguous increase in the areas of raised bogs, accompanied by waterlogging and drying out of adjacent forests.…”
Section: Discussionmentioning
confidence: 99%
“…Excessive moistening coupled with spread of glacial clay soils at the territory make the study area favourable to paludification processes and peat formation. Large areas of the CFSNBR are covered by fens, bogs and paludified forests (Shulze et al, 2002;Puzachenko et al, 2014).…”
Section: Study Sitesmentioning
confidence: 99%
“…Under excessive moistening, some types of bogs exhibit intensive vertical growth, carbon accumulation, and may expand rapidly toward surrounding forests [25]. Modern investigations of [24] using remote sensing data showed that in 1986-2010, in the Central Forest Biosphere Reserve, the total bog area increased from 8% to 10% of the territory. Swamping of territories may result in the increasing instability of the energy balance and entropy production in the landscape of the southern taiga.…”
Section: Discussionmentioning
confidence: 99%
“…The most wide-spread ecosystems in CFBR ( Figure 1) are old spruce forests with a mixture of broad-leaved or small-leaved trees (59% of the core reserve area in 1986 and 49% in 2010), birch or aspen stands and fellings (32% in 1986 and 30% in 2010), restoring spruce forests at windfalls and burnt areas (12% in 2010), and bogs (9% of the core reserve area in 1986 and 11% in 2010) [24]. Puzachenko et al [24] reported that the bog area in the CFBR had increased by 20% in 1986-2010 due to the propagating of bogs toward surrounding forests and the destruction of swampy pine forests.…”
Section: Sites and Datamentioning
confidence: 99%
See 1 more Smart Citation